Além do ponto G, o ponto H: a pornocracia como projeto literário de Hilda Hilst - Bruna Kalil Othero Fernandes (2020)
Through prose, poetry and playwriting, Hilda Hilst (1930-2004) built a monumental literary legacy, debating important themes of human existence, including sex. Although erotic motifs were always part of her poetics, in 1990’s it comes to its aesthetic and thematic apex in the pornographic trilogy: O Caderno Rosa de Lori Lamby, Contos d’escárnio. Textos grotescos and Cartas de um sedutor, essential part of her work and project. From the transgressions made by the author in two instances – work and myth, her literary persona –, a theoretical and analytical discussion has been made over her literary project, according to our hypothesis, a pornocracia (pornocracy), the power of pornography. At the end of the thesis, there is an authorial literary appendix.